Antibiotic Susceptibility Testing of Escherichia coli and Coliform Isolates Detected in Samples of Drinking Water from Central Greece - Nikolaos Tzimotoudis; Antonia Mataragka; Nikolaos D. Andritsos; John Ikonomopoulos (Applied Sciences)
The drinking water cycle consists of the stages of untreated water, potable water, and sewage. Escherichia coli is considered an indicator of the fecal contamination of water since it is a common bacterium of the intestinal flora of humans and warm-blooded animals and is a carrier of many antibiotic resistance genes. The aim of this investigation was to assess the level of drug resistance of coliforms and E. coli isolates in samples of drinking water submitted from various sites of Central South Greece during the period 2018–2022. The highest resistance rates among both E. coli and coliform isolates were observed against ampicillin. The analysis of drug resistance conducted with reference to antibiotic groups indicated that most AMR and/or MDR isolates of E. coli or coliforms exhibited resistance against group A (ampicillin and amoxicillin/clavulanic acid). The most frequent phylogroup of the E. coli isolates was B1 followed by groups A and B2. The genus assignment for the coliform isolates other than E. coli was Enterobacter, Citrobacter, Klebsiella, and Serratia. In conclusion, various bacteria can be transferred from one stage of the drinking water cycle to the next, either through the normal operation of the cycle or due to system failures, with the consequence that even drinking water contains various bacteria, pathogenic or non-pathogenic.